Bark assortments for tall oil production - Isacsson, Patrik (2016)
Fatty and resin acids in bark residues from forest industries can be used to produce high-value green chemicals. Of the assortments investigated, the bark of spruce pulpwood held the highest amount of these compounds with an average yield of 0.9 kg per cubic meter of wood. The variations were found by analysing fresh bark and tree data from homogenous stands of Norway spruce (Picea abies) and Scots pine (Pinus sylvestris). The concentrations of fatty and resin acids in Norway spruce bark showed positive relationships with annual ring increment. The compounds showed negative relationships with both the tree diameter and the bark age as well. The best economical prerequisites for processing the bark were found at pulp mills which only use spruce. Some results support theories about polymerisation of fatty and resin acids due to aging. Since the bark in this study were carefully treated and kept fresh, further research for industrial relevance can preferably focus on the non-fresh bark residues of spruce pulpwood at mill sites.